Grifola frondosa (Maitake) Extract Reduces Fat Accumulation and Improves Health Span in C. elegans through the DAF-16/FOXO and SKN-1/NRF2 Signalling Pathways - Paula Aranaz (MDPI AG, 2021)
In recent years, food ingredients rich in bioactive compounds have emerged as candidates to prevent excess adiposity and other metabolic complications characteristic of obesity, such as low-grade inflammation and oxidative status. Among them, fungi have gained popularity for their high polysaccharide content and other bioactive components with beneficial activities. Here, we use the C. elegans model to investigate the potential activities of a Grifola frondosa extract (GE), together with the underlying mechanisms of action. Our study revealed that GE represents an important source of polysaccharides and phenolic compounds with in vitro antioxidant activity. Treatment with our GE extract, which was found to be nongenotoxic through a SOS/umu test, significantly reduced the fat content of C. elegans, decreased the production of intracellular ROS and aging–lipofuscin pigment, and increased the lifespan of nematodes. Gene expression and mutant analyses demonstrated that the in vivo anti-obesity and antioxidant activities of GE were mediated through the daf-2/daf-16 and skn-1/nrf-2 signalling pathways, respectively. Taken together, our results suggest that our GE extract could be considered a potential functional ingredient for the prevention of obesity-related disturbances.